The Impact of Gadget Usage Habits in Islamic Religious Education Learning on Student Achievements - Kalsum, Ummi; Darmayanti, Darmayanti; Maudin, Maudin (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to examine how the use of gadgets during Islamic religious instruction affects the academic performance of Topa State Elementary School class VIB pupils. As contemporary technical instruments, gadgets are being utilized more and more in the educational process, especially in Islamic Religious Education courses. A quantitative strategy using survey methodology via questionnaires and student learning outcome documentation is the research methodology employed. The study's sample consisted of 25 pupils from Topa State Elementary School's class VIB during the 2024–2025 school year. According to the study's findings, student learning achievement and the amount of time spent using a device for educational purposes are significantly correlated. Properly guided and managed use of technology can enhance comprehension of religious content, whereas unguided use tends to impair focus and academic performance. According to the study's findings, there is a statistically significant relationship between the use of gadgets and the academic performance of class VIB pupils at Topa State Elementary School.